The Spectrum of Vestibular Disorders Presenting With Acute Continuous Vertigo - Yao, Qingxiu; Li, Zhuangzhuang; Xu, Maoxiang; Jiang, Yumeng; Wang, Jingjing; Wang, Hui; Yu, Dongzhen; Yin, Shankai (Frontiers in Neuroscience, 2022)
Objective: To explore composition of vestibular disorders presenting with acute vestibular syndrome (AVS). Methods: We performed a case analysis of 209 AVS patients between January 2016 and December 2020. These patients were grouped into different disorder categories according to the relevant diagnostic criteria. Results: We classified the 209 patients into 14 disorder categories, including 110 cases of vestibular neuritis, 30 of idiopathic sudden sensorineural hearing loss with vertigo, 17 of first attack of continuous vertigo with migraine, 15 of Ramsay Hunt syndrome, 11 of acute labyrinthitis secondary to chronic otitis media, 8 of vestibular schwannoma, 6 of posterior circulation infarction and/or ischemia, 3 of cerebellar abscess secondary to chronic otitis media, 3 of AVS caused by trauma or surgery, 2 of AVS with down-beating nystagmus, 1 of multiple sclerosis of the medulla oblongata, 1 of epidermoid cyst of the posterior cranial fossa, 1 of probable acute otolithic lesion, and 1 of AVS without measurable vestibular dysfunction. Conclusions: A group of disorders present with AVS, and characteristic clinical manifestations and imaging help with accurate diagnosis.